Improving Vocabulary Comprehension Lower Grade Elementary Students: Lawang Sewu Semarang Game Mobile Based on the Teams Games Tournament - Angelika Angelika; Panca Dewi Purwati (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: The lack of innovation in Indonesian language learning media lowers students’ cognitive ability in interpreting vocabulary Indonesian language. This study aims to: 1) analyze learning needs; 2) describe the design of the Lawang Sewu mobile game; 3) describe its feasibility; and 4) describe its effectiveness. Methodology: This study used a research and development (R&D) method based on the Borg and Gall model. Participants were divided into small- and large-scale trial groups. One media expert and one subject expert validated the product. Data were collected through observation, interviews, and questionnaires. Effectiveness was measured using t-tests and N-Gain analysis. Main Findings: The study results revealed that needs analysis through questionnaires, interviews, and observations indicated that current learning does not utilize effective media and requires media development. The media was developed as a digital application with interactive content and visual illustrations. Validation results showed the media was highly feasible, receiving scores of 95% from media experts and 94% from material experts. The effectiveness test confirmed the alternative hypothesis (Ha), with N-Gain scores of 0.71 and 0.77, categorized as high. Novelty/Originality of this study: This research introduces the Lawang Sewu mobile game, an innovative learning media based on the Teams Games Tournament (TGT) model. Its novelty lies in using interactive digital media, rarely applied before, combined with Semarang local stories to enhance low-grade students' vocabulary interpretation in a fun, contextual, and competitive way.